2019
DOI: 10.1039/c9ta00294d
|View full text |Cite
|
Sign up to set email alerts
|

Superior lithium-storage properties derived from a high pseudocapacitance behavior for a peony-like holey Co3O4 anode

Abstract: A unique Co3O4 material, with a peony-like architecture assembled with ultrathin porous nanosheets, could display unprecedented rate capabilities when acting as the anode for lithium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…However, ultrahigh rate capability under a harsh environment is still considerably expected in Sb‐based materials for heavy‐duty SIBs because the application scene of sodium‐ion battery was usually distributed in some high‐power places, such as energy storage power stations and smart grids, etc. As reported in literatures, delicately designed the 2D materials have engrossed increasing attention for SIBs due to the short diffusion path, superior conductivity, and more active sites . For instance, reduced graphene oxide/Sn anode presented much improved rate capability at 20 C .…”
Section: Methodsmentioning
confidence: 95%
“…However, ultrahigh rate capability under a harsh environment is still considerably expected in Sb‐based materials for heavy‐duty SIBs because the application scene of sodium‐ion battery was usually distributed in some high‐power places, such as energy storage power stations and smart grids, etc. As reported in literatures, delicately designed the 2D materials have engrossed increasing attention for SIBs due to the short diffusion path, superior conductivity, and more active sites . For instance, reduced graphene oxide/Sn anode presented much improved rate capability at 20 C .…”
Section: Methodsmentioning
confidence: 95%
“…11,12 To solve these problems, two commonly utilized measures have been used to promote the performance of Co 3 O 4 -based nanocomposites. 13 One is combining Co 3 O 4 with carbonbased materials to form Co 3 O 4 /carbon composite, which can greatly enhance rate capability and conductivity. Simultaneously, the encapsulation of carbon-based materials can slightly relieve the volume change and maintain the mechanical stability of Co 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, like other TMOs materials, Co 3 O 4 suffers from two major defects. The first defect is the severe volume expansion/contraction during the repeated charging/discharging, leading to pulverization of the material and poor cycle stability. The second defect is the inferior electronic conductivity of Co 3 O 4 , leading to poor rate performance. , To solve these problems, two commonly utilized measures have been used to promote the performance of Co 3 O 4 -based nanocomposites . One is combining Co 3 O 4 with carbon-based materials to form Co 3 O 4 /carbon composite, which can greatly enhance rate capability and conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…To provide insight into lithium-storage property of this Fe 3 O 4 @NC material, we deeply investigated electrochemical reaction mechanism rooted in a CV method, which was performed by the above-mentioned cycled cell. In previous literature and our group's works, 10,25,40,41 we have found that there were two types of lithium-storage mechanisms, including conversion reaction and pseudo-capacitance behavior to contribute reversible capacity. Following a previously reported approach, we first obtained the voltammetric curves at different sweep rates (Figure 4a) and then determined the correlativity between the sweep rate and the current response, depending on eq 2: 42,43 = i av b (2) where i is the peak current, v is the sweep rate, and a and b are adjustable values.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 85%
“…Transition-metal oxides (TMOs), as a family of depending on conversion-type reaction mechanism, are very attractive materials, because of their high theoretical capacity (700–1000 mAh g –1 ) and reliable safety within a wide range of voltage. Thus, this family, including magnetite (Fe 3 O 4 ), has shown extraordinary promise for electrochemical energy storage. Unfortunately, their potentials are usually limited, because of poor conductivity, hysteretic kineticsm and unstable structure, particularly volume expansion. To address those formidable issues, a frequently used strategy is to design rational micro/nano architectures, such as nanosheet, nanorod, and hollow structure, etc., which have exhibited a distinct advantage on electrochemical performance, as compared with their bulk counterparts. ,, For example, hierarchical hollow Fe 3 O 4 microspheres prepared by a controlled thermal decomposition route showed high specific capacity and enhanced cycle stability (750 mAh g –1 at 2.8 A g –1 , up to 50 cycles) . As is well-known, a hollow structure has sufficient interior space and, therefore, can accommodate the drastic volume expansion upon lithiation.…”
Section: Introductionmentioning
confidence: 99%